Middle Cambrian through lowermost Ordovician conodonts from Hunan, South China. (24th April 2017) - Dong, Xi-ping; Zhang, Huaqiao
Abstract: Since 1986, samples with a total mass of more than 14, 000 kg, mainly from three key sections in western Hunan, South China, have been processed for conodonts. Previous work mainly focused on biostratigraphy, but the taxonomy has been performed only on the faunas of the middle Cambrian. Described herein are conodonts of the upper Cambrian (Furongian Series) through lowermost Ordovician from Hunan, South China. Conodonts of the middle Cambrian are redescribed, based on material that has been recovered for more than three decades. The fauna consists of 82 species belonging to 36 genera. Newly established genera are Lugnathus n. gen., Miaognathus n. gen., Millerodontus n. gen., Tujiagnathus n. gen., Wangcunella n. gen. and Wangcunognathus n. gen. New species are Coelocerodontus hunanensis n. sp., Furnishina wangcunensis n. sp., Laiwugnathus hunanensis n. sp., Laiwugnathus transitans n. sp., Lugnathus hunanensis n. gen. n. sp., Miaognathus multicostatus n. gen. n. sp., Millerodontus intermedius n. gen. n. sp., Prosagittodontus compressus n. sp., Tujiagnathus gracilis n. gen. n. sp., Wangcunella conicus n. gen. n. sp., Wangcunognathus elegans n. gen. n. sp., Westergaardodina dimorpha n. sp., Westergaardodina gigantea n. sp., and Westergaardodina sola n. sp. The taxonomy of some conodont genera is revised. In the light of histological investigation, genera are assigned to euconodonts, paraconodonts, or protoconodonts. The 13 conodont zones previously proposed in the middle Cambrian through lowermost Ordovician remain the same, but taxa within these conodont zones are documented more clearly because of the revised taxonomy proposed herein.